2007
DOI: 10.1186/1746-4358-2-13
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding practices in a public health field practice area in Sri Lanka: a survival analysis

Abstract: Background: Exclusive breastfeeding up to the completion of the sixth month of age is the national infant feeding recommendation for Sri Lanka. The objective of the present study was to collect data on exclusive breastfeeding up to six months and to describe the association between exclusive breastfeeding and selected socio-demographic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
45
4
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 14 publications
8
45
4
5
Order By: Relevance
“…This is similar to reports from other studies in Nigeria 18 SriLanka 22 and Ireland. 15 This finding is not surprising as it has been demonstrated that high maternal knowledge about infant health benefits from breastfeeding was directly related to maternal intention to exclusively breast feed.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This is similar to reports from other studies in Nigeria 18 SriLanka 22 and Ireland. 15 This finding is not surprising as it has been demonstrated that high maternal knowledge about infant health benefits from breastfeeding was directly related to maternal intention to exclusively breast feed.…”
Section: Discussionsupporting
confidence: 82%
“…It has been demonstrated that women living in urban areas have better knowledge of exclusive breast feeding compared to women in rural areas. [23][24] The59.7% knowledge of exclusive breastfeeding in the present study is higher than 35.3% reported by Abdul Ameer et al 22 in Iraq. The reason for this difference is not immediately clear but may be due to geographical and cultural differences between the two study populations.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Incorrect feeding practices like feeding formula milk or anything other than breast milk and bottle feeding were shown to be significantly associated which must have been due to the poor knowledge on the importance of exclusive BF and the adverse outcomes of formula or other feeds which also showed significant association with difficulties in BF in this study. Two community based study showed similar results 14,17 .…”
Section: Discussionsupporting
confidence: 70%
“…The possible reason for the difference of the results could be that Korea is a country with suboptimal levels of exclusive BF. In our study, employment status and type of family were significantly associated with BF difficulty in contrast to the findings in a community based study 14 . The possible reason could be that our study was done in a hospital setting and not in the community setting.…”
Section: Discussioncontrasting
confidence: 56%